2011
DOI: 10.1016/j.expthermflusci.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the thermal performances of two nanofluids at low temperature in a plate heat exchanger

Abstract: The objective of this study is to compare experimentally the thermal performances of two types of commercial nanofluids. The first is composed of oxides of alumina ((γAl 2 O 3 )) dispersed in water and the second one is aqueous suspensions of nanotubes of carbons (CNTs). The viscosity of the nanofluids is measured as a function of the temperature between 2 and 10°C. An experimental device, containing three thermal buckles controlled in temperature and greatly instrumented permits to study the thermal convectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(58 citation statements)
references
References 18 publications
1
50
0
Order By: Relevance
“…However such a measurement assumed spherical particles resulting in an average value for the length of the particles [27]. It was reported in [10] that the measured average particle size in the CNT nanofluids is much larger than that of the primary nanoparticles suggesting the nanotubes to form clusters in spite of the use of surfactant.…”
Section: Nanofluidsmentioning
confidence: 99%
See 3 more Smart Citations
“…However such a measurement assumed spherical particles resulting in an average value for the length of the particles [27]. It was reported in [10] that the measured average particle size in the CNT nanofluids is much larger than that of the primary nanoparticles suggesting the nanotubes to form clusters in spite of the use of surfactant.…”
Section: Nanofluidsmentioning
confidence: 99%
“…Many previous results are obtained for temperature ranging from 20°C to 60°C. So, there are few studies done at low temperatures [10,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with traditional slid-liquid suspensions containing millimetre or micrometer sized particles, nanofluids as coolants in the heat exchangers have shown better heat transfer performance because of small size of suspend solid particles. Many research groups experimentally reported that the thermal properties of carbon nanotubes CNT suspensions were much higher than those of other nanoparticles with the small volume fraction [4][5][6]. The addition of CNT improves the thermal conductivity of nanofluids but it can also increase the dynamic viscosity and affect the density and the heat capacity.…”
Section: Introductionmentioning
confidence: 99%